Alternative treatment of chemoresistant, recurrent or advanced ovarian cancer. Part II - R. Wilczyński, Jacek; Makuła, Beata (Menopause Review/Przegląd Menopauzalny, 2011)
Lack of satisfactory efficacy of classical chemotherapy in ovarian tumours led to attempts of treatment based on use of small molecules able to modulate or inhibit intracellular pathways engaged in cell growth, proliferation and apoptosis. The paper presents clinical trials in ovarian cancer patients using such drugs as: 1) protein kinase inhibitors, 2) molecules interfering with DNA transcription and repair, 3) inhibitors of transcription factors NF-κB and HIF-1.